A Scoping Review of Challenges and the Adaptation Process in Academia: Implications for Occupational Therapy Educators - Maria Concepcion C. Cabatan; Lenin C. Grajo; Erlyn A. Sana (Scholarworks @ WMU, 2019)
The fulfillment of role expectations and responsibilities as one builds an academic career can be challenging. Increased demand for occupational therapy faculty merits examination of academic experiences from the literature. This study describes the experiences of educators using adaptation models (Savickas & Porfeli, 2012; Schkade & Schultz, 2003) as a theoretical lens. Arksey and O'Malley's Scoping Study Framework (2005) was used in the study. Researchers reviewed literature from 2005 2017 from four databases. Researchers analyzed 28 articles from higher education and the health professions using quantitative and qualitative methods. Twenty-two of the 28 articles were published from 2010-2017. The studies analyzed were conducted in seven different countries, the majority in the US (n = 11) and Australia (n = 7), and more than half used qualitative designs (n = 15). Three themes describe academic experiences: identity-related challenges in academia, process of adaptation among academics, and identification of factors affecting productivity. This study describes the various experiences of faculty to meet the demands of the academic environment. Adaptation of OT academics to their occupational roles and environments has not been widely explored. The implications for future study are discussed.